The Service Link to The Community for NCD Quality Clinic with Performance above Benchmark of Ministry of Public Health in Singburi Province : A Case Study of Diabetes Mellitus - Vihokto, Chanyut; Boonthum, Angsana; Vararuk, Ajchara; Manosoontorn, Supawan (Journal of The Royal Thai Army Nurses, 2021)
This research using a qualitative methods to describe the NCD service delivery linked to the community of NCD quality clinic with performance above benchmark of the Ministry of Public Health in cases of diabetes in every hospital in Singburi Province which was been certified for NCD quality clinic performance in the year 2014, in terms of 1) community organization 2) community health network 3) community population and 4) primary health care system in the community. Data was collected using an in-depth interview tool developed from NCD clinical quality assessment form of the Department of Disease Control. The results found that : 1) Sub-district Administrative Organization (SAO) had sufficient and continuous budget support to the community including plan/project and encouraged people to participate in activities according to the plan/ project as well as encouraged the community to be conducive to good health by creating and providing a place to exercises. 2) Village Health Volunteers (VHV) were the core of health promotion activities, made a plan and home visit of the risk groups and patients to monitor blood sugar levels. In addition, the Diabetes Club organized activities to share and exchange self-care knowledge that improved blood sugar controlling. 3) population in the community has been supported in health care knowledge and various activities by multidisciplinary teams and Diabetes club regularly which improved diabetes patients to have good self-care management skills.4) every hospital operated NCD quality clinic linked to the health promoting hospitals and communities included continuous treatment, reported the diabetes situation of the community, as well assupport SAO and communities to conduct projects/ activities to solve diabetes problems by the community itself.